FAKTOR-FAKTOR PENGGERAK AGRESIVITAS PAJAK PERUSAHAAN PROPERTI DAN REAL ESTATE DI BEI: Capital Intensity, Kepemilikan Manajerial dan Koneksi Politik - Risthi, Alyssa; Novianti, Dian; Silviyani, Yuli Anita (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This study aims to determine the effect of capital intensity, managerial ownership and political connections on tax aggressiveness in property and real estate companies listed on the Indonesian stock exchange in 2014-2021. This research method uses a quantitative method with observational data in the form of panel data which is processed using the help of tools in the form of software E-views version 9. The sample selection in this study uses a purposive sampling approach and a total of 9 companies are obtained. The results of this study indicate the simultaneous effect that capital intensity, managerial ownership and political connections have on tax aggressiveness. Partially managerial ownership has an effect on tax aggressiveness, while capital intensity and political connections partially have no effect on tax aggressiveness.